Using an Online Vocabulary Memorization Tool versus Traditional Vocabulary Exercises - Arif Bakla; Ahmet Çekiç (Mehmet KURUDAYIOĞLU, 2017)
This study was conducted to reveal what Memrise, an online vocabulary study tool, can offer to upper-intermediate EFL learners compared to traditional vocabulary exercises in L2 vocabulary learning. Two groups of upper-intermediate learners (N=80) were randomly assigned to the experimental group and the control group and were given the Vocabulary Knowledge Scale, VKS for short, as the pre-test and post-test. The participants in both groups were exposed to the target vocabulary items in the same reading text. While those in the experimental group created list of target vocabulary items collaboratively in Memrise and then studied the sets individually, the learners in the control group did traditional vocabulary exercises. The results of the post-tests indicated that there was a significant difference between the control group and the experimental group in favor of the experimental group. The researchers discuss possible pedagogical implications of this significant finding for EFL vocabulary instruction.